Layer-by-Layer Self-Assembled Graphene Multilayer Films via Covalent Bonds for Supercapacitor Electrodes - Xianbin Liu; Na Wen; Xiaoli Wang; Yuying Zheng (Nanomaterials and Nanotechnology)
To maximize the utilization of its single-atom thin nature, a facile scheme to fabricate graphene multilayer films via a layer-by-layer self-assembled process was presented. The structure of multilayer films was constructed by covalently bonding graphene oxide (GO) using p-phenylenediamine (PPD) as a covalent cross-linking agent. The assembly process was confirmed to be repeatable and the structure was stable. With the π-π conjugated structure and a large number of spaces in the framework, the graphene multi‐ layer films exhibited excellent electrochemical perform‐ ance. The uniform ultrathin electrode exhibited a capacitance of 41.71 μF/cm2 at a discharge current of 0.1 μA/cm2, and displayed excellent stability of 88.9 % after 1000 charge-discharge cycles.